GLOBAL INTERDEPENDENCE AND FOOD SECURITY: THE IMPACT OF THE RUSSIA-UKRAINE CONFLICT ON INDONESIA - Fitri Al Istiqomah (Kajian Asia Pasifik, 2025)
ABSTRACT Russia-Ukraine conflict has worsened the global food crisis, which had already been impacted by the Covid-19 pandemic. Indonesia has experienced significant increases in food prices and shortages, particularly for wheat, approximately 30% of which is imported from Russia and Ukraine. In addition, Indonesia’s reliance on fertilizer imports about 12% from Russia has further strained the agricultural sector. Although geographically distant from the conflict, Indonesia has felt considerable effects on its food security. This study seeks to answer the research question: how does the Russia-Ukraine conflict affect Indonesia’s food security? Utilizing interdependence theory, this study employs a qualitative approach based on secondary data from archives, documents, and online sources. The findings reveal that Indonesia’s food security vulnerabilities are influenced not only by bilateral ties with Russia and Ukraine, but also by broader global interdependence within the food system. This study contributes to the theoretical understanding of food security under asymmetric interdependence and recommends policy measures such as diversifying import sources and strengthening domestic food production. Keywords: Food Security in Indonesia, Russia-Ukraine Conflict, Interdependence